2023
DOI: 10.3390/cancers15153860
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Care: The “Keystone” of Modern Oncology Practice

Florian Scotté,
Amy Taylor,
Andrew Davies

Abstract: The Multinational Association of Supportive Care in Cancer (MASCC) defines supportive care as “the prevention and management of the adverse effects of cancer and its treatment. This includes management of physical and psychological symptoms and side effects across the continuum of the cancer journey from diagnosis through treatment to post-treatment care. Supportive care aims to improve the quality of rehabilitation, secondary cancer prevention, survivorship, and end-of-life care”. This article will provide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…For these MASCC-ASCO standards of survivorship care, it was acknowledged that survivorship parallels between advanced or metastatic cancers exist, regardless of whether diagnosed de novo or as a result of recurrence or disease progression (i.e., advanced or metastatic cancers can have indolent disease trajectories; periods of disease stability; periods of disease progression with the potential for further treatment; and sudden transitions to end-of-life care [ 4 , 8 ]), and are therefore also congruent with the advanced or metastatic phase of cancer survivorship [ 6 ] as defined by the NCI [see Supplementary File 1 ]. Supportive care was defined in accordance with MASCC, as care provision that seeks to prevent and manage adverse effects of cancer and treatment, including the management of physical and psychological symptoms and side effects across the cancer continuum, from diagnosis through treatment to post-treatment care, with the aim to improve the quality of rehabilitation, secondary cancer prevention, survivorship, and palliative/end-of-life care [ 33 ]. As such, palliative/end-of-life care was also defined in accordance with MASCC as a specialist subset of supportive care that seeks to address serious health-related suffering due to the presence of severe illness, especially for those near the end of life [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these MASCC-ASCO standards of survivorship care, it was acknowledged that survivorship parallels between advanced or metastatic cancers exist, regardless of whether diagnosed de novo or as a result of recurrence or disease progression (i.e., advanced or metastatic cancers can have indolent disease trajectories; periods of disease stability; periods of disease progression with the potential for further treatment; and sudden transitions to end-of-life care [ 4 , 8 ]), and are therefore also congruent with the advanced or metastatic phase of cancer survivorship [ 6 ] as defined by the NCI [see Supplementary File 1 ]. Supportive care was defined in accordance with MASCC, as care provision that seeks to prevent and manage adverse effects of cancer and treatment, including the management of physical and psychological symptoms and side effects across the cancer continuum, from diagnosis through treatment to post-treatment care, with the aim to improve the quality of rehabilitation, secondary cancer prevention, survivorship, and palliative/end-of-life care [ 33 ]. As such, palliative/end-of-life care was also defined in accordance with MASCC as a specialist subset of supportive care that seeks to address serious health-related suffering due to the presence of severe illness, especially for those near the end of life [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Supportive care was defined in accordance with MASCC, as care provision that seeks to prevent and manage adverse effects of cancer and treatment, including the management of physical and psychological symptoms and side effects across the cancer continuum, from diagnosis through treatment to post-treatment care, with the aim to improve the quality of rehabilitation, secondary cancer prevention, survivorship, and palliative/end-of-life care [ 33 ]. As such, palliative/end-of-life care was also defined in accordance with MASCC as a specialist subset of supportive care that seeks to address serious health-related suffering due to the presence of severe illness, especially for those near the end of life [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Digital counseling services offer convenient access to mental health professionals, helping patients cope with the emotional challenges often accompanying a cancer diagnosis. Palliative care resources, accessible through digital health, guide managing pain and improving quality of life, offering comfort and support to patients and their families [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…Despite advances in the diagnostic and therapeutic fields, over 50% of patients with cancer eventually die of the disease [2]. Additionally, the survivors deal with a wide array of morbidities caused by the disease itself, as well as treatment-related toxicities [3]. These points altogether denote a need for biomarkers aiding in treatment escalations in patients with a poorer prognosis and de-escalations to mitigate toxicities in patients with a lower-risk disease.…”
Section: Introductionmentioning
confidence: 99%
“…The RMH prognostic score, which includes albumin level, lactate dehydrogenase (LDH) level, and number of metastases, was initially introduced by Arkenau et al as a prognostic score to optimize patient selection for phase I clinical trials, often involving highly selected patient groups [7]. They found that patients with a low RMH score (0-1) had a significantly longer median overall survival (OS) of 33 weeks compared to 15.7 weeks for patients with a high RMH score (2)(3). After that, the prognostic value of the RMH score for predicting outcomes was explored for various cancers on phase 1 trial cohorts, as well as a few cohorts from real-world settings [8,9].…”
Section: Introductionmentioning
confidence: 99%